Effect of pharmacist-led interventions on blood pressure among adult Asian patients with hypertension: a systematic review and meta-analysis - Delgado, Shevvie Belle L; Guinto, Mikaela Gail M; Hawili III, Armando Arnold G; Gloria, Mac Ardy J (Faculty of Pharmacy, 2025)
The expanding role of pharmacists in patient-centered care prompted investigation of its effectiveness in hypertension management; however, data are inconsistent and less generalizable to the Asian population. This study aimed to determine the effect of pharmacist-led interventions on the blood pressure (BP) of adult Asian patients with hypertension, compared to no pharmacist-led intervention. Five databases, grey literature, and hand search were used to locate articles from inception to September 2023. We included randomized controlled trials among adult Asian patients with hypertension receiving pharmacist-led intervention versus no pharmacist-led intervention, reporting changes in systolic and diastolic BP (SBP & DBP) from all languages. Study quality was assessed with Cochrane Risk of Bias tool, results analyzed qualitatively and quantitatively per PRISMA guidelines, meta-analysis conducted with random-effects model, heterogeneity explored through subgroup analysis, and publication bias assessed through funnel plots. From 11,914 studies, 14 studies were analyzed. Results show the most common pharmacist-led intervention was educational intervention (n=13, 92.86%); pharmacist-led interventions significantly decreased SBP by -5.15 mmHg (95% CI: -8.43, -1.88) and DBP by -2.59 mmHg (95% CI: -4.85, -0.32). Subgroup analysis revealed healthcare setting, number of interventions investigated, non-use of technology, predominant sex, country income status, and prevailing level of education affect SBP and DBP lowering. Findings should be used with caution due to various sources of heterogeneity, moderate- to high-risk of bias, and potential publication bias. The findings support optimization of hypertension management via pharmacist-led interventions.